The Impact of Hajj on the Society of Bangladesh - Md Thowhidul Islam (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2018)
Millions of Muslims from around the world including Bangladesh pour perform Hajj every year. Being the largest gathering of the Muslims, the Hajj has got immense socio-economic and cultural impacts on every Muslim society as well as Bangladesh. Hajj develops a unique symbol of unity, equality, universality, co-existence, brotherhood, indiscrimination, peace and tolerance, through performing common rituals, among the individuals, societies and nations belonging to different races, castes, ethnicities, colors, and languages, which create differences in everyday life of human beings. Bangladeshi Hajjis’ views towards women are more positive as gender interaction is a natural part of Hajj, while it is uncommon in the country. The positive teachings of Hajj particularly of pure Aqidah, produced several revolutionary movements in Bengal such as the Faraidi movement of Hajji Shariatullah with the aim of purifying Muslim society from superstitious Aqidah and practices. Hajj works as a social platform of getting together for Bangladeshi people at Makkah and Madinah. Hajj has developed the private tour operating industries in Bangladesh to facilitate the Hajjis. Transaction of billions of dollars takes place commercially during Hajj, while many commodities are exchanged informally. The Hajjis enjoy a very special dignity and status in the society of Bangladesh. Hajj creates an inter-cultural amalgamation combining various elements of different cultures particularly of Arabian. Hajj increases knowledge of the Hajjis both experimental and theoretical through various means. Bangladeshi Hajjis consider Hajj as the preparation for death; and thus try to remain isolated from the worldly activities and observe the religious duties strictly. This transformative property enables the Hajjis to pursue a more purified life and they become a model of spirituality and religiosity. Hajj not only moulds the Hajjis into sincere and practicing Muslims, but also the society at large with their honesty and piety. Thus, Hajj brings immense impacts on the society, economy, education, religiosity and culture of Bangladesh. This chapter is aimed at analyzing the socio-economic and religio-cultural impacts of Hajj on the society of Bangladesh. It also included the perspectives of the society with a view to better understanding the influence of Hajj on the Hajjis, non-Hajjis and the society at large.